Hubungan Sedentary Lifestyle terhadap Minat Olahraga pada Peserta Didik Sekolah Dasar - Darmawan, Syamsul; Wibowo, Tito Parta; Zahra, Siti Fatimahtun; Erfandy, Wahyu; Muhaimin, Ali; Sari, Dini Permata (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Activity carried out after sleeping is called sedentary behavior. Therefore, to engage in sports activities, we must have the intention or desire for these sports activities to be carried out. This non-experimental quantitative research does not control or manipulate the variables. The study was conducted on elementary school students in Lalabata District. The population in this study was all sixth-grade students in 4 schools in Lalabata District, and sampling used purposive sampling with a sample of 108 students. After data collection, the data were analyzed using Spearman's rank correlation. The results of the 2-tailed sig. have a sig. 2-tailed value > 0.05, which is 0.08. Therefore, from these calculations, it can be concluded that there is no relationship between a sedentary lifestyle and sports interest in sixth-grade elementary school students in Lalabata District. Thus, it can be concluded that there is no relationship between a sedentary lifestyle and sports interest in sixth-grade elementary school students in Lalabata District. Researchers can use the findings of this study to identify the relationship between sedentary lifestyle and other variables that may influence and relate to each other.